2016
DOI: 10.1177/1602400302
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Femoral Tunnel Length with Body Height, Limb Length, and Thigh Length in Indian Patients Undergoing Anterior Cruciate Ligament Reconstruction

Abstract: Purpose. To measure the femoral tunnel length created through a far medial portal and determine its correlation with body height, limb length, and thigh length in 404 Indian patients undergoing anterior cruciate ligament (ACL) reconstruction. Methods. 364 male and 40 female Indian patients aged 18 to 51 (mean, 26.8) years underwent ACL reconstruction by a single surgeon using the hamstrings tendon autograft. Their body height, limb length, and thigh length were measured by a single assessor, as was the femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
4
2
Order By: Relevance
“…Several authors have reported on femoral tunnel length, a summary of which can be found in table 2 (Table 2) [27,28,29,30,31,32,33,34]. Regarding femoral tunnel length, the results of the present study do not differ significantly from those of previous reports.…”
Section: Accepted Manuscriptcontrasting
confidence: 51%
See 3 more Smart Citations
“…Several authors have reported on femoral tunnel length, a summary of which can be found in table 2 (Table 2) [27,28,29,30,31,32,33,34]. Regarding femoral tunnel length, the results of the present study do not differ significantly from those of previous reports.…”
Section: Accepted Manuscriptcontrasting
confidence: 51%
“…Being able to determine the appropriate femoral tunnel length prior to surgery can reduce the risk of creating an insufficient femoral tunnel. Several authors have reported on femoral tunnel length [27,28,29,30,31,32,33,34]. However, to our knowledge, no studies have addressed the correlation between femoral tunnel length and body size and knee morphology in anatomical double-bundle ACL reconstruction.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Transportal technique was used to make femoral tunnel in all cases in both the groups [22]. Group 1 had patients who got operated with hamstring free graft [23] (Technique 2) and groups 2 patients got operated with hamstring graft with preserved insertion [16] (Technique 1).…”
Section: Methodsmentioning
confidence: 99%